The Mind-Body Problem: The Perspective of Psychology - Kreitler, Shulamith (Scientific Research, 2018)
The paper traces the changes in the conceptualization of body-mind relations in psychology in terms of five sequential phases. The first phase is characterized by the view that there is nothing but the body. The second phase is marked by the conception that the mind is the only relevant agent. The third phase is based on the view that both body and mind exist but are on parallel tracks. The main assumption in the fourth phase is that both body and mind exist and function in interaction. Finally, the major tenet of the fifth phase is that body and mind are identical. The role and status of cognition, emotion, and behavior in the five phases are discussed. The paper presents for each phase the main theoretical constructs and implications for empirical studies, as well as major research products and insights yielded in the frameworks defined in terms of each phase.
Keywords: Cognition; Emotion; Behavior; Interaction; Identity